Crushing behaviour of Li4SiO4 and Li2TiO3 ceramic particles - Mingzhun Lei; Qigang Wu; Shuling Xu; Jian Wang (Nuclear Materials and Energy, 2022)
The crushing behaviour of certain ceramic particles–such as Li4SiO4 and Li2TiO3 have been investigated herein, which are considered to be ideal particles for use in the pebble-bed structure of tritium breeding blankets. For such granular materials, the material properties, fracture and fragmentation evolution, and fracture strength are of primary concern. This paper discusses these parameters and their impacts on the particle properties, taking into account the results from experimentation and numerical simulations. The benchmark tests on these ceramics have reflected the mechanical properties of the relative materials, which can also be used to validate the methodology of the finite element (FE) simulation method. The validated method was then used to simulate the crushing behaviour of the two candidate particles during the compression process. The largest stress appeared at the contact point of the loading plate and increased gradually from the contact point to the centre of the sphere, before final failure. It can clearly be observed from the obtained stress–strain curve that the two particles have three similar stages throughout the compression process, including crack generation, expansion, internal stress release, and breakage. The detailed crack evolution of the two types of particles studied was analysed using the calibrated FE method.